ArCatch: uma solução para verificação estática de conformidade arquitetural do tratamento de exceção - Meneses Filho, Juarez de Lima (2016)
Exception handling is a common error recovery technique employed to improve software robustness. However, studies have reported that exception handling is commonly neglected by developers and is the least understood and documented part of a software project. The lack of documentation and difficulty in understanding the exception handling design can lead developers to violate important design decisions, triggering an erosion process in the exception handling design. Architectural conformance checking provides means to control the architectural erosion by periodically checking if the actual architecture is consistent with the planned one. Nevertheless, available approaches do not provide a proper support for exception handling conformance checking. To fulfill this gap, this work proposes ArCatch: an architectural conformance checking solution to deal with the exception handling design erosion. ArCatch provides: (i) a declarative domain-specific language for expressing design constraints regarding exception handling; and (ii) a design rule checker to automatically verify the exception handling conformance. The usefulness and effectiveness of the approach was evaluated in an evolution scenario composed by 10 versions of an existing web-based Java system. Each version was checked against the same set of exception handling design rules. Based on the results and the feedback given by the system’s software architect, the ArCatch proved useful and effective in the identification of existing exception handling erosion problems and locating its causes in the source code.